Предмет: Алгебра,
автор: li1713
Ответы
Автор ответа:
0
7.
6 - 10 : 10 - 2с+2 = 6 - 2с+2 - 10 * (с-1)(с+1) =
с-1 (с-1)² с²-1 с-1 с-1 с-1 (с-1)(с-1) 10
=6-2с-2 - с+1 = 4-2с-с-1 = 3-3с = 3(1-с) = -3(с-1) = -3
с-1 с-1 с-1 с-1 с-1 с-1
8. х²≥64
х²-64≥0
(х-8)(х+8)≥0
х=8 х=-8
+ - +
-------- -8 --------- 8 ----------
\\\\ \\\\
Ответ: 4)
6 - 10 : 10 - 2с+2 = 6 - 2с+2 - 10 * (с-1)(с+1) =
с-1 (с-1)² с²-1 с-1 с-1 с-1 (с-1)(с-1) 10
=6-2с-2 - с+1 = 4-2с-с-1 = 3-3с = 3(1-с) = -3(с-1) = -3
с-1 с-1 с-1 с-1 с-1 с-1
8. х²≥64
х²-64≥0
(х-8)(х+8)≥0
х=8 х=-8
+ - +
-------- -8 --------- 8 ----------
\\\\ \\\\
Ответ: 4)
Автор ответа:
0
Спасибо огромной )))
Похожие вопросы
Предмет: Русский язык,
автор: Andrey870901
Предмет: Физика,
автор: Аноним
Предмет: Математика,
автор: rashidovaziyoda64
Предмет: Алгебра,
автор: Вильдан1234